2016
DOI: 10.1007/s10334-015-0515-2
|View full text |Cite
|
Sign up to set email alerts
|

Correction of B 0-induced geometric distortion variations in prospective motion correction for 7T MRI

Abstract: Objective Prospective motion correction can effectively fix the imaging volume of interest. For large motion, this can lead to relative motion of coil sensitivities, distortions associated with imaging gradients and B0 field variations. This work accounts for the B0 field change due to subject movement, and proposes a method for correcting tissue magnetic susceptibility-related distortion in prospective motion correction. Materials and methods The B0 field shifts at the different head orientations were chara… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 53 publications
2
18
0
Order By: Relevance
“…Several previous studies have reported on the magnitude of the B 0 field changes caused by head motion based on either measurement or simulation (17,29,30,38,28). The values were either similar, or substantially higher than the values found here.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported on the magnitude of the B 0 field changes caused by head motion based on either measurement or simulation (17,29,30,38,28). The values were either similar, or substantially higher than the values found here.…”
Section: Discussionmentioning
confidence: 99%
“…A static shimming procedure is typically performed prior to the functional scan, which attempts to counteract the overall magnetic field inhomogeneity in the target region without differentiating the sources of the corresponding contributions. Motion of the head relative to the rest of the body and the shimming coils results in the manifestation of complex magnetic field inhomogeneities (Ooi et al, 2013b; Yarach et al, 2016). Furthermore, rotation of the head about any axis non-parallel to the main magnetic field direction causes the field deviations arising from head tissues to change; they do not simply move in synchrony with the head (Maclaren et al, 2013; Ooi et al, 2013b), as can be seen in Figure 1.…”
Section: Influence Of Motion On Fmri Datamentioning
confidence: 99%
“…This apparent motion complicates the application of retrospective intensity and gradient non-linearity correction; however it does not change anything regarding the underlying MR physics. Therefore accurate compensation of these effects is feasible upon the application of the appropriate (known at the time of image reconstruction) spatial transformations (Yarach et al, 2016, 2015). …”
Section: Common Pitfalls Associated With Prospective Motion Correctionmentioning
confidence: 99%
“…Besides the coil sensitivity estimation, regularization also plays an important role in iterative reconstructions. It not only enables noise suppression, but also stabilizes the convergence at high iteration counts . Moreover, our results in Figure c show that the smoothing effect caused by large λ appears relatively small, and the activation is only slightly broadened compared to the activation map obtained from the small λ.…”
Section: Discussionmentioning
confidence: 71%
“…bold-italicF denotes the discrete Fourier transform. The Tikhonov regularization with a tridiagonal (1 –2 1) regularization matrix ( bold-italicL) was used to reduce noise and stabilize the solution at high iteration counts . The regularization parameter ( λ) is a positive real number.…”
Section: Methodsmentioning
confidence: 99%